2012
DOI: 10.1590/s0100-40422012000500023
|View full text |Cite
|
Sign up to set email alerts
|

Voltammetric determination of sibutramine in beverages and in pharmaceutical formulations

Abstract: Recebido em 6/10/11; aceito em 30/11/11; publicado na web em 23/1/12 A simple and sensitive method has been proposed for the determination of sibutramine-HCl in energy drinks, green tea and pharmaceutical formulations using differential pulse voltammetry performed on a hanging mercury drop electrode. In the chosen experimental condition (Mcllvaine pH 4.0 buffer, 50 mV pulse amplitude and 40 mV s -1 scan velocity), sibutramine-HCl presented a reversible behavior and a peak maximum at -80 mV. Detection limit was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Although many analytical techniques have been reported for the determination of sibutramine in natural product samples used for weight‐loss , only a few methods have been applied to slimming tea beverages . Fast and low‐cost methods using electroanalytical techniques have been used for sibutramine determination in tea samples based on the voltammetric detection at a boron‐doped diamond electrode (BDDE) or a hanging mercury drop electrode (HMDE) . Beside these electrodes, a modified glassy carbon electrode (GCE) using microextraction‐assisted voltammetry of microparticles with multivariate chemometric techniques was reported for screening in adulterated tea beverages .…”
Section: Introductionmentioning
confidence: 99%
“…Although many analytical techniques have been reported for the determination of sibutramine in natural product samples used for weight‐loss , only a few methods have been applied to slimming tea beverages . Fast and low‐cost methods using electroanalytical techniques have been used for sibutramine determination in tea samples based on the voltammetric detection at a boron‐doped diamond electrode (BDDE) or a hanging mercury drop electrode (HMDE) . Beside these electrodes, a modified glassy carbon electrode (GCE) using microextraction‐assisted voltammetry of microparticles with multivariate chemometric techniques was reported for screening in adulterated tea beverages .…”
Section: Introductionmentioning
confidence: 99%
“…Carvalho et al have reported the voltammetric investigation of SHM at a hanging mercury drop electrode (HMDE) and its determination in beverages and pharmaceutical formulations. 26 This method involves the use of mercury based electrodes. The electrochemical behavior of SHM at bare GCE and modied GCE (ERGO-GCE) has not been studied so far, neither has its evaluation as a sensor to quantify SHM by differential pulse voltammetry been attempted.…”
Section: Introductionmentioning
confidence: 99%
“…Structurally sibutramine is an amine (pKa = -8.5) and, consequently, can be detected in an acidic environment, where sibutramine will be positively charged. 15 Several BGEs with different compositions (phosphate, borate buffers) over a wide pH range (2-12) were studied. The pH of the buffer was adjusted with 1.0 mol L −1 sodium hydroxide or 1.0 mol L −1 phosphoric acid.…”
Section: Preliminary Analysismentioning
confidence: 99%